2004
DOI: 10.1007/978-3-540-24595-7_2
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Crossing Minimization Heuristics

Abstract: Abstract. We present an extensive experimental study of heuristics for crossing minimization. The heuristics are based on the planarization approach, so far the most successful framework for crossing minimization. We study the effects of various methods for computing a maximal planar subgraph and for edge re-insertion including post-processing and randomization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
1
37
0
2
Order By: Relevance
“…For the computation of heuristic values we used the planarization approach. Gutwenger and Mutzel presented an extensive computational study of crossing minimization heuristics [9]. The authors investigate the effects of various methods for the computation of a maximal planar subgraph and different edge re-insertion strategies for the planarization approach.…”
Section: Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the computation of heuristic values we used the planarization approach. Gutwenger and Mutzel presented an extensive computational study of crossing minimization heuristics [9]. The authors investigate the effects of various methods for the computation of a maximal planar subgraph and different edge re-insertion strategies for the planarization approach.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Pre-and post-processing procedures have been developed to improve the solution quality. A computational study on state-of-the-art heuristics can be found in [9].…”
Section: Introductionmentioning
confidence: 99%
“…In crossing minimization, the problem is to find a drawing with the minimum number of crossings. The problem is NP-Complete [8] but there has been a great deal of research on heuristic algorithms [9]. Graph planarization [13] is often used together with careful reinsertion of edges.…”
Section: Related Workmentioning
confidence: 99%
“…Later, and rather surprisingly, it was shown in [14] that there exists a linear-time algorithm, using the SPQR-tree datastructure, which finds the optimal insertion path for e over all possible planar embeddings of H. In [13] it was shown that this approach is in practice vastly superior to the former in terms of the overall obtained number of crossings.…”
Section: Introductionmentioning
confidence: 99%